2021
DOI: 10.1111/jpn.13533
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to iron oxide nanoparticles is associated with ferroptosis in the brain: A chicken embryo model analysis

Abstract: Ferroptosis is a name coined in 2012 for cell death driven by irondependent devastating lipid peroxidation (Shen et al., 2018). It is distinct from other cell death modes, including apoptosis and necrosis, in underlying mechanism, morphology and function in normal cell life (Yang & Stockwell, 2016). Ferroptotic cells appear with round cytoplasm and the normal nuclear size and chromatin density under light microscopy (Xie et al., 2016). From a mechanism perspective (Figure 1c), ferroptosis can be induced throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Additionally, to verify the presence of a nanosized component in the particle population, we performed an ARM analysis that highlighted the presence of a small portion of nanosized magnetite agglomerates in the sample that would have been administered to zebrafish embryos. Subsequently, in agreement with previous studies [ 27 , 39 ], we established that the exposure of fish embryos to magnetite concentrations up to 400 µg/mL does not affect embryo viability, as it does not induce morphological defects in key tissues/organs. With the great advantage of embryo transparency presented by the zebrafish model, we were able to measure in vivo the redox state within the brain of magnetite-treated fishes, confirming a dose-dependent increase in ROS levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, to verify the presence of a nanosized component in the particle population, we performed an ARM analysis that highlighted the presence of a small portion of nanosized magnetite agglomerates in the sample that would have been administered to zebrafish embryos. Subsequently, in agreement with previous studies [ 27 , 39 ], we established that the exposure of fish embryos to magnetite concentrations up to 400 µg/mL does not affect embryo viability, as it does not induce morphological defects in key tissues/organs. With the great advantage of embryo transparency presented by the zebrafish model, we were able to measure in vivo the redox state within the brain of magnetite-treated fishes, confirming a dose-dependent increase in ROS levels.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, in vitro studies have suggested that iron oxide nanoparticles, including magnetite, can cross the placental barrier, reaching the embryo and inevitably affecting its development [ 25 , 26 ]. One study performed in chicken revealed that maternal exposure to magnetite allowed these particles to reach the embryo, causing damaging cerebral effects [ 27 ]. Nevertheless, at the present time, no evidence has shown whether cleavage fragments detaching from coarse magnetite particles or elemental Fe released by coarse magnetite particles can affect brain cell formation processes during development.…”
Section: Introductionmentioning
confidence: 99%